The German legacy in East Central Europe as recorded in recent German-language literature - Glajar, Valentina (Studies in German literature, linguistics, and culture., 2004)
This study focuses on the complex legacy of the German and Austrian political and cultural presence in East Central Europe in the twentieth century. It contributes to the discussion of 'German' identity in eastern Europe, and has important implications for German, Austrian, and East European studies. It addresses the specific situations of the former Habsburg regions of Bukovina (the Ukraine/Romania), Moravia (the Czech Republic), and Banat (Romania) as illustrated in contemporary literature by German-speaking authors, such as Herta Müller, Erica Pedretti, Gregor von Rezzori, and Edgar Hilsenrath. The works of these authors constitute contrastive historiographic narratives of the multiethnic regions of East-Central Europe under a series of oppressive regimes: first Austrian imperialism, and then German and Romanian fascism in Bukovina; National Socialism in Moravia, and Communism in Romania. Valentina Glajar investigates these narratives as representations of multicultural East Central Europe in German-language literature that show the political and ethnic tensions between Germans and local peoples that marked these regions throughout the 20th century, often with tragic consequences. The study thus expands and diversifies the understanding of German literature and challenges the concept of a homogeneous German identity reaching far beyond the borders of the German-speaking countries. Valentina Glajar is assistant professor of German at Southwest Texas State University.